Kontribusi Pemikiran Hukum Islam dan Moderasi Beragama terhadap Upaya Deradikalisasi Sosial - Sufi'y, Mhd; Ja'far, A. Kumedi (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2025)
Islamic legal thought and religious moderation play an important role in responding to the challenges of radicalization in society. Radicalization, which often arises from narrow, literal, and textual understandings of religion, frequently threatens social harmony and security stability. This paper aims to analyze how the principles of inclusive Islamic law and the approach of religious moderation can serve as solutions in addressing and responding to the issues and practices of radicalization. Through a qualitative approach and literature study, this research examines basic concepts in Islamic law and wasathiyyah (moderation) that emphasize equality, balance, justice, and tolerance. Religious moderation, as a paradigm that stresses contextual and adaptive religious understanding, is also explained as an effort to counter extremist and fundamentalist narratives. The research findings indicate that the integration of progressive Islamic legal thought and religious moderation can create a more inclusive and tolerant society toward radical ideologies. This article concludes that religious education that prioritizes moderate values and a holistic understanding of religion is a strategic step in preventing radicalization and promoting social peace in accordance with religious teachings.